Pelatihan Pembuatan Paving Block Sesuai Standar Mutu SNI di Desa Sukaharja Kabupaten Ketapang - Sartika, Sartika; Herman, Herman; Aqla, Syarifah; Herkan Afandi, Idris; Firman, Firman; Santi, Maya; Mastura, Syarifah; Indra Septiansyah, Sy. (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2024)
The Paving block is a building material product made from cement which is used as an alternative cover or hardening of the ground surface. The use of paving blocks is currently continuing to increase for application on footpaths, sidewalks, yards or parking lots, and residential complex roads. This is because paving blocks have the advantage that they are easy to install and do not require heavy equipment in the installation process. The Ketapang State Polytechnic Service Team will carry out community service by providing training and direct demonstrations on making paving blocks according to SNI standards to the community of RT 05 RW 01 Sukaharja Village, Ketapang Regency. The training activities began with remarks from the Coordinator of the D-III Mining Technology Study Program, a brief presentation of material by the PKM team, and practice of making paving blocks using a press tool. This activity was carried out in Gang Lobak RT 05 RW 01, Sukaharja sub-district, Ketapang Regency. The achievement of the training objectives can be seen during the delivery of material and practice of making paving blocks where participants were very enthusiastic in asking questions and discussing how to make and the correct composition to obtain SNI standard paving block.